Molly Haynes: capstone - Haynes, Molly, artist (Colorado State University. Libraries, 2023)
The artist's statement: "Her Spirit…Reflections" explores the feelings of grief and loss from a hopeful and nostalgic perspective. Through multiple mediums, I explore what it means it to find peace and joy through the creative process. Clay and paint are materials that hold memory; memory of its shape, the artists' mark, the collective moment in time, of where it has been, how it has traveled and its purpose. They hold the memories of ancestral stories, how people have thrived or survived. In its fired state, clay holds the memory of the practice and the process. It tells so many different stories, nourishing the body, representing the body, containing the body. Similarly, the process of painting are many moments and marks, frozen in time. I use a traditional style of painting to create a feeling of dream-like nostalgia using symbols close to my heart, in relation to my late mother, who passed from early on-set Alzheimer's in 2006. I explore the beauty in missing someone so profoundly and the memories I carry. Rather than dwelling in how the pain makes me feel, I aim to share the joy from having felt that love. The poet, Ross Gay reminisces on the sensation of seeing birds flying in the airport as something he must share with others by saying, "I wonder if this impulse to share, the urge to elbow your neighbor until the bird flew between you up into the pipes and rafters you did not notice until you followed the bird there, is also among the qualities of delight? And further, I wonder if this impulse suggests- and this is just a hypothesis, though I suspect there is enough evidence to make it a theorem- that our delight grows as we share it." This is the sentiment I aim to bring into everything I create, whatever medium that may be. Each clay feather is a representation of motherly spirit, essence and the memory of her. The shadows that the feathers make are not unlike a memory; intangible and existing only because the form exists somewhere in time. They are a reminder of loss and grief but also grace and beauty. Attached to the physical body of the vessel, the feathers become weighted and grounded. They become personal, bodily, and intimate. The forms represent an opposition between spirit and physical. The spirit of the feather, a collection of her memories, lives simultaneously in the ether and the body, where one is formless and the other is bound by change. The paintings of the owls represent a deep connection to spirit, a reminder that they are close and always watching. Not only are they close through our memories, but maybe also through something much harder to comprehend. Clay and painting have given me the space to reflect on emotions and experiences that I have a hard time putting into words. Multi-media artist, Rose B. Simpson, reminds us that we are all guests on our earth, in our bodies and in this space. With that knowledge, I am honored to have been a guest in my mother's home, and now a guest in the memory of her. This is a reminder to hold space for gratitude as I am given the opportunity to honor her through my personal expression. This space is a meant to be a place of reflection for myself and anyone else. We aren't alone in our losses and grief; these emotions are communal. Remember that the greatest grief comes from what has given you the greatest joy.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting